2018
DOI: 10.1590/1806-9061-2017-0579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hatching Time on Yolk Sac Percentage and Broiler Live Performance

Abstract: This study investigated the effects of broiler chick hatching time on the percentage of the yolk sac and subsequent broiler live performance. Broiler hatching eggs were obtained from a commercial flock at 55 wk of age and were stored for 2 d at 18°C and 75% relative humidity (RH) prior to incubation. Chicks were identified as hatching Early (471-477 h), Middle (480-486 h), and Late (494-510 h). All chicks were removed from the trays at 510 h of incubation. Body weight (BW) and yolk weight (YW) were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
6
12
0
Order By: Relevance
“…At time of hatch, BW was highest ( P = 0.007) for late hatchers, lowest for early hatchers, and intermediate for middle hatchers ( Table 2 ). This finding is in agreement with the studies of Lamot et al (2014) and Özlü et al. (2018) who also found that earlier hatching chicks were lighter than later hatchers.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…At time of hatch, BW was highest ( P = 0.007) for late hatchers, lowest for early hatchers, and intermediate for middle hatchers ( Table 2 ). This finding is in agreement with the studies of Lamot et al (2014) and Özlü et al. (2018) who also found that earlier hatching chicks were lighter than later hatchers.…”
Section: Resultssupporting
confidence: 93%
“…Chicks from the late HWP had lower ( P = 0.012) yolk-free BW (79.92 g) and higher ( P = 0.025) relative yolk weight (2.65%) compared to those from the early HWP (85.33 g and 2.17%, respectively), while middle HWP was intermediate. Similar observations were made by Özlü et. al.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies reported that prolonged storage resulted in an increase in the incubation time ( Elibol et al., 2002 ; Reijrink et al., 2010 ; Dymond et al., 2013 ) and that egg storage caused some live chicks to be rejected only because they hatched later ( Nicholson, 2012 ). In addition, chick quality and broiler live performance were reduced in late-hatched chicks compared with early- and middle-hatched chicks ( Özlü et al., 2018b ). Therefore, the overall results of the present study indicate that higher prewarming temperatures could be used as a method to decrease late-hatching chicks and improve overall chick quality in eggs stored for a long period.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, chicks being held in the hatcher for an extended period of time can lead to dehydration, diminished yolk sac reserves ( Hager and Beane, 1983 ), reduced BW ( Hager and Beane, 1983 ; Wyatt et al., 1985 ), and increased mortality before and after placement ( Misra and Fanguy, 1978 ). Reduced growth and increased early mortality in chicks held without access to feed and water were associated with dehydration and a shortage of available energy ( Vieira and Moran, 1999b ), but holding chicks in the hatcher for 24 h has been reported to not clinically dehydrate chicks or affect live performance ( Casteel et al., 1994 ; Joseph and Moran, 2005 ; Almeida et al., 2006 ; Lamot et al., 2014 ; Özlü et al., 2018 ). Work with respect to posthatch holding has often varied in that chicks were placed at or later than 24 h apart, but they were subsequently weighed on the same day in some experiments ( Fanguy et al., 1980 ; Hager and Beane, 1983 ; Wyatt et al., 1985 ; Pinchasov and Noy, 1993 ; Vieira and Moran, 1999a ) or on the basis of days on feed in other studies ( Careghi et al., 2005 ; Almeida et al., 2006 ; Lamot et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%